A low complexity selective mapping OFDM using multiple IFFT stages. (11th September 2008) - Ghassemi, A.; Gulliver, T. Aaron
A low complexity Selective Mapping (SLM) technique for reducing the Peak-to-Average Power Ratio (PAPR) of an Orthogonal Frequency Division Multiplexing (OFDM) signal is introduced. The intermediate signals within an N-point IFFT using a radix Decimation In Time (DIT) or Decimation In Frequency (DIF) IFFT algorithm are used to generate the phase sequences. It is shown that DIF provides lower multiplicative complexity in generating the SLM sequences compared to DIT, with the same PAPR reduction. In addition, a high radix FFT algorithm provides better PAPR reduction performance per stage with less multiplicative complexity compared to a low radix algorithm. We further reduce the computational complexity by proposing a low computational complexity technique based on multiplying the phase sequences at multiple IFFT stages. This new technique greatly reduces the multiplicative complexity while providing similar PAPR reduction to Ordinary SLM (O-SLM). The additive complexity is also reduced.